Lampu Jalan Otomatis Memanfaatkan Turbin Angin Sebagai Penerangan di Area Pantai Bagan Asahan - Fauzy Maulana Sinaga; Herman Saputra; Elly Rahayu (Jurnal Pendidikan Informatika (EDUMATIC), 2022)
Bagan Asahan Beach is one of the attractions in Tanjung Balai which is visited by many visitors. At night, Bagan Asahan beach is very dark, making it prone to sexual violence or crime. The purpose of this research is to make automatic street lights utilizing wind turbines as lighting in the Bagan Asahan beach area. The method used is a prototype with the stages of collecting information by interviewing visitors and local village administrators, making and repairing prototypes and conducting prototype trials. The hardware in the tool testing consists of arduino nano, DC motor, relay, led lamp, SMD led, LDR, ultrasonic, battery and inverter. Our findings show that the tool that was built has an error if the battery is = 50% then the two sensors do not read the signal accurately. Overall, the tool can function properly although there are still some shortcomings..